Visually guided respiratory motion management for Ethos adaptive radiotherapy. Issue 1 (25th October 2021) - Kim, Taeho; Ji, Zhen; Lewis, Benjamin; Laugeman, Eric; Price, Alex; Hao, Yao; Hugo, Geoffrey; Knutson, Nels; Cai, Bin; Kim, Hyun; Henke, Lauren
Abstract: Purpose: Ethos adaptive radiotherapy (ART) is emerging with AI‐enhanced adaptive planning and high‐quality cone‐beam computed tomography (CBCT). Although a respiratory motion management solution is critical for reducing motion artifacts on abdominothoracic CBCT and improving tumor motion control during beam delivery, our institutional Ethos system has not incorporated a commercial solution. Here we developed an institutional visually guided respiratory motion management system to coach patients in regular breathing or breath hold during intrafractional CBCT scans and beam delivery with Ethos ART. Methods: The institutional visual‐guidance respiratory motion management system has three components: (1) a respiratory motion detection system, (2) an in‐room display system, and (3) a respiratory motion trace management software. Each component has been developed and implemented in the clinical Ethos ART workflow. The applicability of the solution was demonstrated in installation, routine QA, and clinical workflow. Results: An air pressure sensor has been utilized to detect patient respiratory motion in real time. Either a commercial or in‐house software handled respiratory motion trace display, collection and visualization for operators, and visual guidance for patients. An extended screen and a projector on an adjustable stand were installed as the in‐room visual guidance solution for the closed‐bore ring gantry medical linear accelerator utilized by Ethos. Consistent respiratory motion traces and organ positions on intrafractional CBCTs demonstrated the clinical suitability of the proposed solution in Ethos ART. Conclusion: The study demonstrated the utilization of an institutional visually guided respiratory motion management system for Ethos ART. The proposed solution can be easily applied for Ethos ART and adapted for use with any closed bore‐type system, such as computed tomography and magnetic resonance imaging, through incorporation with appropriate respiratory motion sensors.